Analisis Nilai Tahanan Isolasi dan Tegangan Tembus pada Minyak Transformator 150 kV Sebelum dan Sesudah Purifikasi di PT Energi Listrik Batam - Purba, Jhon Hericson; Safriandi, Muhammad Suharian (JURNAL INTEGRASI, 2024)
Transformers are critical components in electricity transmission, and system failures can be catastrophic. PT Energi Listrik Batam has a 150 kV power transformer that experienced an oil leak in the Low Voltage section in September 2023. Transformer oil serves as an insulating material. Insulation Resistance and Breakdown Voltage tests showed a decline in oil quality, with an insulator value of 50 kV. PT Energi Listrik Batam conducted oil purification to restore its quality. Purification removes gases and particles that degrade oil quality. As a result, after purification, the insulation resistance and breakdown voltage of the transformer oil increased to 80 kV.